IMPACT OF EUROPEAN INTEGRATION PROCESSES ON THE NECESSITY OF LONG-TERM BUDGET PLANNING INTRODUCTION IN UKRAINE - Ganna Muzychenko (Baltic Journal of Economic Studies, 2017)
The Association Agreement between Ukraine and the European Union was ratified in September 2014. Ukraine has undertaken to implement and enforce EU standards, including in the financial sphere, which are regulated by international law. The purpose of the study is to determine the impact of European integration processes on the necessity of the long-term budget forecasting process introduction into the budget process of Ukraine and the revelation of special budgetary rules regulated this process in the EU. The methodology. The list of requirements (budget procedures and rules) for their introduction by law into the budget process of Ukraine was determined based on the generalization and systematization of normative legal acts that regulate the medium-term financial planning as the EU standard. The results showed that the long-term budget forecast developing procedure in the budget process will allow the government to timely identify the unfavourable trend in the state’s fiscal policy and introduce preventive measures, determine the full scale of economy’s and business’ reaction to the reforms’ introduction and new laws adoption, estimate fiscal space for fiscal policy implementation for coming years, take into consideration the budget forecast’s indicators during the annual adoption of budget decisions. The study defines the difference between the budget forecast and the planned budget: the forecast is for five years and more, the plan is for one year only; forecast indicators are not mandatory for implementation, they are only guidelines, and planned indicators are mandatory for implementation; the budget forecast is approved by the order of the Cabinet of Ministers of Ukraine and annually specified, the planned budget (for the current budget year) is approved by the Verkhovna Rada of Ukraine by adopting the relevant law, amendments are an exception and also approved by law. The practical implementation. Governments of countries that systematically undertake long-term budget forecasts have developed effective measures to ensure the state sustainable development through the pension systems’ restructuring or the creation of special funds for future needs. Publicity and availability of information about long-term sustainable development trends is a prerequisite for obtaining public support and confidence from the government’s efforts to reduce the long-term budgetary tension.